Pengaruh Iklan dan Promosi Penjualan di Instagram terhadap Keputusan Pembelian Produk Serum Wajah Scarlett Whitening - Yohanah Natalia; Herman; Chasan Azari (Journal Of Accounting and Business, 2022)
Advertising and sales promotion is one of the promotional activities that may be carried out during the Covid-19 pandemic. Scarlett Whitening is a local skincare brand that is in great demand by Instagram users. Currently, Scarlett Whitening is the brand with the most Instagram followers compared to other local skincare Instagram followers. This study aims to determine how much influence advertising and sales promotions on Instagram have on purchasing decisions for Scarlett Whitening facial serum products. The population in this study are Scarlett Whitening consumers. The sample in this study were 100 respondents. This type of research is quantitative. Sources of data used are primary data and secondary data. Data collection techniques using a questionnaire with five alternative answers. The stages carried out in this research are validity and reliability tests. Then to test the hypothesis, multiple linear regression tests were carried out, then the individual parameter significance test (t statistical test), simultaneous significance test (f statistical test), the coefficient of determination (R2) and multiple correlation coefficients were carried out. The results of the regression analysis in this study indicate that advertising and sales promotions have an effect on purchasing decisions with the equation Y= 2.531 + 0.236 X1 + 0.534 X2. Sales promotion variable is the most influential variable on purchasing decisions, which is equal to 0.534. The advertising variable is the variable that has the least effect on purchasing decisions, which is 0.236. The results of the f (simultaneous) test show that the advertising and sales promotion variables have an effect on purchasing decisions